Reconsideration of "A Fast Computational Algorithm for the Discrete Cosine Transform" - Zhongde Wang (IEEE transactions on communications, 1983)
Some corrections are made for the original paper "A fast computational algorithm for the discrete cosine transform," 1 which contains some errors of indexes and of multiplication factors.